2021
DOI: 10.1186/s13195-020-00759-3
|View full text |Cite
|
Sign up to set email alerts
|

Topographic patterns of white matter hyperintensities are associated with multimodal neuroimaging biomarkers of Alzheimer’s disease

Abstract: Background White matter hyperintensities (WMH) are frequently found in Alzheimer’s disease (AD). Commonly considered as a marker of cerebrovascular disease, regional WMH may be related to pathological hallmarks of AD, including beta-amyloid (Aβ) plaques and neurodegeneration. The aim of this study was to examine the regional distribution of WMH associated with Aβ burden, glucose hypometabolism, and gray matter volume reduction. Methods In a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 52 publications
1
52
0
Order By: Relevance
“…Studies assessing the association between S‐CC WMH and AD pathologies (amyloid or tau) provided mixed results. A link was found between S‐CC WMH and cerebrospinal fluid (CSF) Aβ 1‐42 80 and amyloid‐PET, 81 but not CSF phosphorylated tau, 80 while a recent study found a significant association between global WMH and plasma total tau 82 . Cerebral amyloid angiopathy may at least partially explain the association between WMH and AD as well as the posteroanterior gradient of WMH in AD 83–85 .…”
Section: Discussionmentioning
confidence: 96%
“…Studies assessing the association between S‐CC WMH and AD pathologies (amyloid or tau) provided mixed results. A link was found between S‐CC WMH and cerebrospinal fluid (CSF) Aβ 1‐42 80 and amyloid‐PET, 81 but not CSF phosphorylated tau, 80 while a recent study found a significant association between global WMH and plasma total tau 82 . Cerebral amyloid angiopathy may at least partially explain the association between WMH and AD as well as the posteroanterior gradient of WMH in AD 83–85 .…”
Section: Discussionmentioning
confidence: 96%
“…White matter degeneration is closely related to cognitive and functional decline and may occur years before the onset of anticipated symptoms of AD ( Ble et al, 2006 ; Lee et al, 2016 ; Zavaliangos-Petropulu et al, 2019 ). White matter degeneration is recognized as a prominent characteristic and potential biomarker of AD ( Sachdev et al, 2013 ; Lee et al, 2016 ) and correlates with neuroimaging biomarkers of AD ( Gaubert et al, 2021 ). Oligodendrocyte lineage cells dysfunction is a crucial mechanism of the white matter changes of AD and may be the potential target ( Nasrabady et al, 2018 ; Lorenzini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study sample comprised 43 cognitively unimpaired older adults (OA), 18 participants with subjective cognitive decline (SCD) and 34 participates with mild cognitive impairment (MCI). By including participants along the cognitive continuum with normal cognition, SCD, and MCI, we ensured that there was enough variance due to VRF and brain pathology, including of Aβ and WMH, in our sample ( Wirth et al, 2018 ; Gaubert et al, 2021 ) to assess the proposed associations. Other important reasons to include the asymptomatic or preclinical stages (i.e., SCD and MCI) are that these are clinically relevant in terms of early treatment and some mechanisms may specifically appear in stages before the onset of clinical symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The WMH volumes were derived using probability maps, which were computed from segmented FLAIR images using the lesion prediction algorithm (LPA), implemented in the Lesion Segmentation Toolbox (LST 2 , version 2) of SPM12. As described in our previous studies ( Garnier-Crussard et al, 2020 , 2021 ; Gaubert et al, 2021 ), processing comprised the co-registration of individual raw FLAIR images to their respective T1-weighted image and the computation of native-space lesion probability maps. To quantify WMH volumes, native-space lesion probability maps were binarized at a threshold at 0.5 and a minimal cluster size of 10 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation